Laser and vision sensing for obstacle avoidance and target seeking for a simple mobile robot - Akmeliawati, Rini; Demidenko, Serge; Menon, Anuradha (Inderscience Enterprises Ltd., 2009)
In this paper the use of laser and vision sensing for navigation of a simple fully-autonomous mobile robot capable of performing obstacle detection and avoidance functions is presented. The navigation system uses image processing and laser triangulation computation to detect obstacles on the path towards the pre-specified target. It then employs fuzzy logic to determine the movements of the robot to avoid the obstacles while to continuously progressing towards the target. A localization system of the robot is based on progressive calculation and updating of global (world) and object coordinates. The system is implemented using inexpensive commodity hardware and employs simple but effective data processing software and control algorithms.